Estrutura de uma floresta tropical na Amazônia Mato-Grossense sob manejo florestal - Silva, Sandra Susi Alves da (2023)
The present work aimed to characterize the floristic composition, the horizontal, vertical, diametric structures of a primary vegetation with the formation of a Semideciduous Seasonal Forest in the Amazon covered by forest management. The study area is located in Juína, North Mesoregion of Mato Grosso, micro-region of Aripuana, state of Mato Grosso (1123hectares), where 12491 trees with dbh ≥ 30 cm were measured. Calculated in the floristic composition, the Shannon-Wener Diversity (H'), Simpson (C), Pielou Equability (J’)and Species Richness indexes; In the horizontal structure, the indexes of density or abundance, dominance, frequency, Importance value and Cover value index; In the vertical structure, the phytosociological value, Sociological Position and Extended Importance Value; and in the diametric structures, the estimates of volumes by DBHs class and species groups. Part of 35 genera, 18 families and 44 species. In the floristic composition, the botanical families Fabaceae stood out, followed by Vochysiaceae and Lauraceae, confirming the trend in other studies for this plant typology. The Shannon-Wiener index (H') was 2.992, which means that the area has low diversity, the Simpson index (C) was 0.923, showing the dominance of few species, Qualea sp, Ocotea acutângula, Erisma uncinatum, dominating the community covering study, the Pielou equability index (J’) was 0.78, indicating average floristic diversity. In the horizontal structure, 11 trees ha-1 , indicating low density. These results explain why the forest tends to be homogeneous. For basal area were estimated 57,6 m². ha-¹Species with IVI between 1% and 15%, represent 66% of all species. Other studies with the same plant typology confirm this trend. For the vertical structure, in the lower stratum, 38 species are presented, represent 84.4%, in the middle stratum, 100% of the species were represented, and in the upper stratum, trees with a size above 16 m, about 73.33 % of species are presented. For the relative value of phytosociological position (PFR), Erisma uncinatum stood out with 39.81%, Hymeneae sp with 17.02% and Peltogyne sp with 15.46%. In the diametric analyses, the total number of trees by diameter classes, presented the classic inverted-J distribution.